Gain enhancement and RCS reduction of CP patch antenna using partially reflecting and absorbing metasurface. Issue 2 (17th February 2019) - Sharma, Ankit; Gangwar, Deepak; Kumar Kanaujia, Binod; Dwari, Santanu
ABSTRACT: This paper presents a novel partially reflecting and absorbing metasurface (PRAM) in order to reduce Radar Cross Section (RCS) and enhance the gain of the circularly polarized patch antenna. The unit cell of PRAM consists of two stacked substrates with metallic patterns, which is used to design absorbing surface (AS) and partial reflecting surface (PRS). The metallic pattern on the top of the two substrates acts as AS and absorbs most of the out of band incoming wave. The bottom surface of the PRAM is used as PRS to construct Fabry-Perot (F-P) resonance cavity with metamaterial ground plane (MGP) for gain enhancement. Simulated and measured results show that the peak gain of the proposed antenna is enhanced by 5.7 dB at 6.6 GHz. The results also show that the impedance bandwidth and 3-dB axial ratio bandwidth of the antenna are also improved by the employment of PRAM. Monostatic RCS of the proposed antenna is significantly reduced in the broad range of 7 to 18 GHz and proposed antenna achieves maximum RCS reduction of 15.6 dB at 14.3 GHz.